Sistem Presensi Dosen Menggunakan Rfid Untuk Mendukung Administrasi Pendidikan Tinggi Berbasis Less Contact Pada Masa Pandemi Covid-19 - T. Muhammad Johan (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2021)
The Covid-19 pandemic that has hit the world over the past 2 years has changed the paradigm and behavior of people, no matter what in Indonesia. Various policies implemented by the government in preventing the spread of the Covid-19 virus, one of which is by implementing health protocols such as maintaining distance, washing hands and wearing masks. In addition, the government has also implemented a policy to study from home, where the policy is considered to have an impact on reducing the number of positive cases of Covid-19. However, the authors assess that this policy has not had a maximum impact, because administratively it is still not supported by the application of technology that is able to apply the Less Contact concept. In this study, a lecturer attendance system was developed using Web-based RFID as a system that can support the administration of higher education that is Less Contact. The result is that the attendance system that has been tested is considered capable of supporting health protocols in universities because lecturers can input attendance by attaching an RFID-based ID Card without having to crowd in queues to fill out the attendance list and use the same pen together as in the old system which is very expensive. at risk of transmitting the virus between fellow lecturers